Investigation of a Salmonellosis Outbreak Caused by Multidrug Resistant Salmonella Typhimurium in China - Xiang, Ying; Li, Fuxiang; Dong, Nian; Tian, Sai; Zhang, Haoran; Du, Xinying; Zhou, Xuan; Xu, Xuebin; Yang, Hongxia; Xie, Jing; Yang, Chaojie; Liu, Hongbo; et al. (Frontiers in Microbiology, 2020)
The rapid emergence of multidrug resistant Salmonella is a global public-health concern as outbreaks in recent years have mostly been caused by multidrug resistant strains. Here we evaluated an outbreak in China caused by multidrug resistant Salmonella enterica serovar Typhimurium (S. Typhimurium) by employing an epidemiological and laboratory investigation using conventional methods and whole genome sequencing (WGS). Eleven of the 12 people who participated in a banquet showed gastrointestinal symptoms, and 8 S. Typhimurium strains were recovered. Isolated outbreak strains showed multidrug resistance (MDR), and decreased susceptibility to ciprofloxacin, a first-line drug recommended by WHO for clinical treatment of intestinal infections. Antimicrobial resistance (AMR) gene analysis indicated that the MDR phenotype of these outbreak strains may be due to the presence of a number of AMR genes, including the blaOXA-1 and blaTEM-1 β-lactamase genes, which are often plasmid-borne and easily transferred. Further virulence gene analysis indicated that these outbreak strains also carried a large number of virulence genes, including 2 types of Salmonella pathogenicity islands (SPI-1 and SPI-2) and many adhesion-related virulence genes. Cluster analysis based on pulse-field gel electrophoresis data and phylogenetic analysis based on WGS revealed that the outbreak clone was closely related to and thus probably derived from local strains. This outbreak caused by multidrug resistant S. Typhimurium highlights the need for government improved strategies for the prevention and control of Salmonella infections.